Exploring the effects of combined nostalgic activities and music therapy on Alzheimer's disease outcomes - Zhang, Yunqiu; Wang, Yunqiong; Liu, Qiao; Xiao, Jun; Huang, Ling; Zhou, Lan; Liu, Xuemei (Frontiers in Psychology, 2025)
ObjectiveExploring the effects of combination of nostalgic activity-based therapies, including music therapy on cognitive function, negative emotions, and sleep quality in patients with mild to moderate Alzheimer's disease.MethodsA total of 63 patients with mild to moderate Alzheimer's disease who were treated at the Sichuan Provincial Psychiatric Center of the People's Hospital of Sichuan Province from January to June 2023 were selected as the research subjects. They were randomly divided into a study group (n = 31) and a control group (n = 32) using a random number table method. The control group received routine treatment and nursing care, while the study group received nostalgic music therapy intervention on the basis of the control group. The Mini Mental State Examination (MMSE), Montreal Cognitive Assessment Scale (MOCA), Self Rating Anxiety and Depression Scale (SAS, SDS), and Pittsburgh Sleep Quality Index (PSQI) of the two groups were compared.ResultsA total of 30 cases from each group completed the study. After 12 weeks of intervention, the MMSE and MOCA scores of both groups of patients increased, and the treatment group was higher than the control group (P < 0.05); SAS, SDS and PSQI scores decreased compared with those before intervention, and the treatment group was lower than the control group (P < 0.05).ConclusionNostalgic music therapy can improve cognitive function, alleviate negative emotions, and improve sleep quality in patients with mild to moderate Alzheimer's disease.